Carbon-related Materials in Recognition of Nobel Lectures by Prof. Akira Suzuki in ICCE - Kaneko, Satoru; Mele, Paolo; Endo, Tamio; Tsuchiya, Tetsuo; Tanaka, Katsuhisa; Yoshimura, Masahiro; Hui, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Details recent scientific advances in the field of carbon materials and carbon nanomaterials including: polymers, carbon nanocomposites, and graphene; Covers a wide spectrum of topics related to carbon science, from organic chemistry to devices, physical chemistry, applied physics, synthesis, and device implementation; Describes experimental and theoretical approaches in several categories of carbon-related materials. This book summarizes the recent advances in carbon-related materials. It covers both experimental and theoretical approaches in graphene and nanocarbon materials, carbon composites and thin films, organic synthesis and physical chemistry, and characterization tools. Also discussed are cutting-edge applications for use in biochemical assays, dental implant surface modifi cations, pressure sensors, and more. This book is published in recognition of the Nobel Lectures delivered by Akira Suzuki, Emeritus Professor of Hokkaido University and Nobel Prize winner in Chemistry, 2010.
Part I: GRAPHENE AND NANOCARBON MATERIALS -- Chapter1: The Synthesis and the Catalytic Properties of Graphene-based Composite Materials -- Chapter2: Optical characterization of graphene and its derivatives - an experimentalist's perspective -- Chapter3: Submerged liquid plasma for the formation of nanostructured carbon -- Chapter4: Lab on a Graphene -Functionalized Graphene Transistor and Its Application for Biochemical Assay -- Chapter5: Production of single- and few-layer graphene from graphite -- Chapter6: Graphene-based coatings for dental implant surface modification -- Part II: CARBON COMPOSITES AND THIN FILMS -- Chapter7: Effect of CNT on the Mechanical Properties of Composite Materials and Structures -- Chapter8: Energy absorption capability of hybrid fibers reinforced composite tubes -- Chapter9: Graphene Rubber Nanocomposites: Preparation, Structure and Properties -- Chapter10: Effects of Graphene and Graphite on Properties of Highly Filled Polybenzoxazine Bipolar Plate for Proton Exchange Membrane Fuel Cell: A Comparative Study -- Chapter11: Electrical Properties of Amorphous Carbon Nitride Thin Films for Pressure Sensor applications -- Part III: ORGANIC SYNTHESIS AND PHYSICAL CHEMISTRY -- Chapter12: Combination of cross-coupling and metal carbene transformations for the development of new multicomponent reactions -- Chapter13: Synthetic molecular springs: Stretched and contracted helices with their interconversions of mono-substituted polyacetylenes prepared with a rhodium complex catalyst -- Chapter14: The Spin Coupling in the Polyaromatic Hydrocarbons and Carbon-based Materials -- Chapter15: Electrocatalytic Hydrogen Production Properties of Polyaniline doped with Metal Organic Frameworks -- Chapter16: Plasma Bonding of Plastic Films -- Part IV: CHARACTERIZATION TOOL -- Chapter17: Atomic Force Microscopy for Characterizing Nanocomposites.
Keywords: Ceramic materials; Nanochemistry; Polymers; Nanotechnology; Ceramics; Nanochemistry; Polymers; Nanotechnology